CHOOSING THE OPTIMAL TREATMENT METHOD FOR URETHRAL STRICTURES IN MEN (Ta'limning zamonaviy transformatsiyasi, 2025)
Annotation: This reviews the various treatment methods for urethral strictures in men, a condition that causes narrowing of the urethra, leading to difficulty in urination. The study examines different therapeutic approaches, including conservative management, endoscopic treatments, and surgical interventions. The article discusses the indications, advantages, limitations, and outcomes associated with each treatment method. It emphasizes the need for personalized treatment plans based on the location, length, and severity of the stricture, as well as patient factors such as age, comorbidities, and lifestyle. The article also highlights the importance of early diagnosis and the role of advanced technologies in improving treatment outcomes. The findings suggest that a combination of techniques, such as balloon dilation or urethrotomy followed by urethroplasty, can offer the best long-term results for most patients.